2007
DOI: 10.1152/ajpheart.00947.2007
|View full text |Cite
|
Sign up to set email alerts
|

Acetaminophen-mediated cardioprotection via inhibition of the mitochondrial permeability transition pore-induced apoptotic pathway

Abstract: Our laboratory has previously reported that acetaminophen confers functional cardioprotection following cardiac insult, including ischemia/reperfusion, hypoxia/reoxygenation, and exogenous peroxynitrite administration. In the present study, we further examined the mechanism of acetaminophen-mediated cardioprotection following ischemia/reperfusion injury. Langendorff-perfused guinea pig hearts were exposed to acute treatment with acetaminophen (0.35 mM) or vehicle beginning at 15 min of a 30-min baseline stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 47 publications
2
19
0
Order By: Relevance
“…We observed that SDF-1 did not decrease LDH levels compared with vehicle group, implying that SDF-1-improved cardiac function is unlikely through reduction of necrotic cell death. Being consistent with our findings, more and more recent studies (13,16,31) have demonstrated that decreasing apoptosis and apoptotic signaling are able to protect I/R-induced cardiac dysfunction by using a Langendorff model.…”
Section: Discussionsupporting
confidence: 93%
“…We observed that SDF-1 did not decrease LDH levels compared with vehicle group, implying that SDF-1-improved cardiac function is unlikely through reduction of necrotic cell death. Being consistent with our findings, more and more recent studies (13,16,31) have demonstrated that decreasing apoptosis and apoptotic signaling are able to protect I/R-induced cardiac dysfunction by using a Langendorff model.…”
Section: Discussionsupporting
confidence: 93%
“…Since the mitochondrial permeability transition pore (mPTP) opening plays a critical role in the pathogenesis of reperfusion injury, it is possible that resveratrol prevents reperfusion injury by inhibiting the pore opening. Therefore, we then determined if resveratrol could prevent the mPTP opening by detecting changes in light absorbance (Hadzimichalis et al, 2007). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The current model is that ApAP protects the heart against myocardial infarction via inhibition of the mitochondrial permeability transition pore and consequent cell death (Hadzimichalis et al , 2007). However, the mechanism of action of ApAP remains unknown.…”
Section: Discussionmentioning
confidence: 99%